THE REALISTIC DEPICTION OF POVERTY AND URBAN LIFE - Eldorbek Erkin og’li Khamitov; Markabaeva Mexriban Keulimjayevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper examines how literature realistically portrays poverty and life in urban areas. Realist writers focus on ordinary people and their daily struggles, showing how poverty influences every part of life, including work, family, education, and health. Cities are described in detail, with crowded streets, poor living conditions, and the difficulties people face in urban environments. The study shows that characters in realist fiction often experience financial problems, unemployment, and social inequality. Through their experiences, writers reveal how poverty limits opportunities, affects personal relationships, and creates social challenges. Realist authors also highlight the differences between social classes, showing the gap between the rich and the poor and demonstrating how society can be unfair and difficult to navigate. Urban life is portrayed as both a place of opportunity and a source of struggle. Writers describe neighborhoods, streets, workplaces, and social interactions to make the setting realistic and vivid. Poverty is also connected to moral issues, such as crime, corruption, and social responsibility, which adds depth to the stories. In conclusion, realist fiction uses the depiction of poverty and urban life to show real social problems. It allows readers to understand human struggles and the effects of inequality. By presenting life in cities and the hardships of poor people, realist writers encourage empathy and reflection, making these works valuable for understanding society.